Green themes in architectural curriculum – scope and content - Saja Kosanović; Branislav Folić (Igra Ustvarjalnosti, 2013)
The significance of environmental factor in the course of searching for optimal space solutions on architectural and urbanistic level is increasing and the theme can no longer be excluded from the creation process. Green aspect penetrates the design in its various phases and scales, starting from early conceptual ideas. The knowledge is, therefore, necessary. Where from do architects learn about green themes: books and magazines, media, specialized courses organized by various nongovernmental organizations or do they acquire necessary knowledge at school? The aim of this paper is to propose educational green themes, their necessary scope, depth and content and suitable methods to transfer knowledge to the students of architecture and then to, based on the set criteria, examine curricula of different schools of architecture. The results of comparative analysis give an answer on current variable presence of green themes in architectural educational curricula on international level.